2013
DOI: 10.3390/molecules181215541
|View full text |Cite
|
Sign up to set email alerts
|

Stereocontrolled Synthesis and Functionalization of Cyclobutanes and Cyclobutanones

Abstract: Abstract:In the last decade a certain number of new cyclobutane and cyclobutanone synthesis and functionalization protocols have been published. Organo-and biocatalyzed eco-friendly approaches to cyclobutane-containing molecules have been developed with interesting results. Also, successful new total synthesis of bioactive compounds and drugs have been recently reported where a four membered ring represented the key intermediate. Therefore, the rising interest in this field represents a great point of discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(22 citation statements)
references
References 131 publications
0
21
0
1
Order By: Relevance
“…However,w ithin the last decade there has been asubstantial increase in the number of reports in this area. [2] These reactions are significant because they provide an efficient route to access the cyclobutane scaffold, require simple and readily available alkene chemical inputs,and are completely atom-economical (Scheme 1a). [3,4] Furthermore,the products are important for several reasons: 1) Cyclobutanes and cyclobutenes are extremely useful intermediates for chemical synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However,w ithin the last decade there has been asubstantial increase in the number of reports in this area. [2] These reactions are significant because they provide an efficient route to access the cyclobutane scaffold, require simple and readily available alkene chemical inputs,and are completely atom-economical (Scheme 1a). [3,4] Furthermore,the products are important for several reasons: 1) Cyclobutanes and cyclobutenes are extremely useful intermediates for chemical synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, catalytic enantioselective [2+2] cycloadditions are significantly less investigated. However, within the last decade there has been a substantial increase in the number of reports in this area 2. These reactions are significant because they provide an efficient route to access the cyclobutane scaffold, require simple and readily available alkene chemical inputs, and are completely atom‐economical (Scheme ) 3.…”
Section: Introductionmentioning
confidence: 99%
“…Dagegen sind katalytische enantioselektive [2+2]‐Cycloadditionen deutlich weniger untersucht. Allerdings nahm die Zahl der Publikationen auf diesem Gebiet in den letzten 10 Jahren erheblich zu 2. Diese Reaktionen sind von Bedeutung, denn sie bieten einen effizienten Zugang zum Cyclobutangerüst, benötigen einfache und leicht erhältliche Alkene als Ausgangsverbindungen und sind vollkommen atomökonomisch (Schema ) 3.…”
Section: Introductionunclassified
“…Asymmetric synthesis of diverse chiral cyclobutanes remains as ignificant challenge. [11] Previous attempts to enantioselectively functionalize cyclobutyl CÀH bonds require the installation of adirecting group. [12] Through ligand screening, we found that the mono-protected aminoethyl amine (MPAAM) ligand (L1)w as promising for enantioselective CÀHa ctivation of cyclobutane carboxylic acid, affording am oderate yield and enantioselectivity.…”
mentioning
confidence: 99%